ASSESSING CONSTRAINTS TO NEWCASTLE DISEASE VACCINE (I2) ADOPTION AMONG SMALLHOLDER LOCAL CHICKEN FARMERS IN PLATEAU STATE, NIGERIA - Apeh, D.; Hassan A. B.; Jibril, S. A.; Garba, M.; Haruna, V.; Haruna. I. M. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
This study examined the constraints to Newcastle disease vaccine adoption among local chicken farmers in Plateau State, Nigeria. A multistage simple random sampling technique was used to select 369 farmers across the three agricultural zones. Data were collected through the administration of questionnaire and analysed using Garrett’s ranking method. The results indicated that inadequate veterinary extension services with a mean score of 65.53 pose the greatest challenge, followed by mistrust in regulatory bodies and vaccinators (59.30), and the availability of vaccine substitutes with score of 59.30 and 58.89, respectively. The study concluded that inadequate veterinary extension services was the major constraints to adoption of Newcastle disease NDV-I2’s among local chicken farmers in the study area. The study recommended that addressing these barriers requires strengthening veterinary extension services through targeted investment in education and farmers’ support and promoting awareness of NDV-I2’s economic and health benefits and fostering trust in regulatory institutions through transparency and engagement are essential. Finally, improving vaccine supply chains and market regulations will enhance NDV-I2 availability and reduce reliance on suboptimal alternatives.